167k views
1 vote
Solve the equation below for x

3(x+2) = 8(x - 1)+5

explain it using any of these vocab words:
polynomial expressions
graphing polynomial expressions
dividing polynomials
solving polynomial equations
rational functions

1 Answer

3 votes

Answer: x = 9/5

Explanation:

You want to apply the distributive property to both of these "polynomial expressions." You get 3x + 6 = 8x - 8 +5

Subtract 5 from both polynomials to get 3x + 1 = 8x - 8.

Subtract 1 from both polynomials to get 3x = 8x - 9

Subtract 8x from both polynomials to get -5x = -9

Finally divide both polynomials by -5 to get x = 9/5

User Cpm
by
5.3k points